Baby, don't hurt me : stories and scars from Saturday night live - Kattan, Chris, 1970-; Thrasher, Travis, 1971- (BenBella Books, Inc., 2019)
"SNL veteran Chris Kattan offers a look behind the scenes and at his personal life, complete with celebrity-filled stories and photos"--